2017
DOI: 10.1016/j.amc.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

5-regular oriented graphs with optimum skew energy

Abstract: Let G be a simple undirected graph and G σ be the corresponding oriented graph of G with the orientation σ. The skew energy of G σ , denoted by ε s (G σ ), is defined as the sum of the singular values of the skew adjacency matrix S(G σ ). In 2010, Adigawhere ∆ is the maximum degree of G of order n. In this paper, we determine all connected 5-regular oriented graphs of order n with maximum skew-energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Thus the skew energy was defined as the sum of the absolute values of all eigenvalues of the skew adjacency matrix of an oriented graph. In 2017, Guo et al [16] determined all connected 5-regular oriented graphs with maximum skew-energy. In 2018, Deng et al [7] found all tournaments achieving the minimum skew energy.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the skew energy was defined as the sum of the absolute values of all eigenvalues of the skew adjacency matrix of an oriented graph. In 2017, Guo et al [16] determined all connected 5-regular oriented graphs with maximum skew-energy. In 2018, Deng et al [7] found all tournaments achieving the minimum skew energy.…”
Section: Introductionmentioning
confidence: 99%